Konsep Garapan Tari Ngetam Padi - Perawati, Perawati (PPSDP Undergraduate Journal of Educational Sciences, 2025)
The Ngetam Padi dance is a traditional dance that depicts the process and excitement of the community in welcoming the season of ngetam padi. This dance is often performed as an expression of gratitude for the abundant harvest of ngetam and is a form of respect for nature and the gods who are believed to give blessings for the ngetam. This dance also reflects the agricultural life of the people who are very dependent on rice as the main food source. The Rice Ngetam Dance is a work of art inspired by the experience of rice drumming in the midst. This aims to measure the level of knowledge of farmers and entrepreneurs. Through observations and reflections on farmers’ lives, this work depicts the ngetam process which is full of challenges and success. In this work, the theme of Ngetam Padi is raised as a representation of the resilience and spirit of an agricultural society. Rice is the staple food source of the Indonesian people.